2021
DOI: 10.1126/sciadv.abj2099
|View full text |Cite
|
Sign up to set email alerts
|

Geographically targeted COVID-19 vaccination is more equitable and averts more deaths than age-based thresholds alone

Abstract: COVID-19 mortality increases markedly with age and is also substantially higher among Black, Indigenous, and People of Color (BIPOC) populations in the United States. These two facts can have conflicting implications because BIPOC populations are younger than white populations. In analyses of California and Minnesota-demographically divergent states-we show that COVID vaccination schedules based solely on age benefit the older white populations at the expense of younger BIPOC populations with higher risk of de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 43 publications
0
67
0
Order By: Relevance
“…Access and equity issues are as important as public trust in vaccines. Initially, neighborhoods with high vaccination rates had a greater share of White and Asian people and a lower share of Black and Latino people ( Sacarny and Daw, 2021 ), reinforcing that prioritization of high-risk racial/ethnic groups is needed to ensure equitable access ( Wrigley-Field et al, 2021 ). Equity in vaccination rates is critical to ensure that COVID-19 health disparities are reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Access and equity issues are as important as public trust in vaccines. Initially, neighborhoods with high vaccination rates had a greater share of White and Asian people and a lower share of Black and Latino people ( Sacarny and Daw, 2021 ), reinforcing that prioritization of high-risk racial/ethnic groups is needed to ensure equitable access ( Wrigley-Field et al, 2021 ). Equity in vaccination rates is critical to ensure that COVID-19 health disparities are reduced.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed age-specific analysis revealed that particularly those below the age of 20 had the highest increased uptake, followed by those 20-29 years, holding for both first and second doses. When introduced and incentives in particular settings (nightclubs, events >1,000 people), higher uptake was found mainly in the youngest age group in Switzerland and when certification was extended to broader settings (events >30 people, entire hospitality sector, leisure activities) and increase was also observed in older groups (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Certification alone is not a silver bullet to increase vaccine uptake, with other measures such as geographically targeted interventions being more effective for certain groups. 30 Limitations include a lack of access to granular daily age-based uptake for all countries and ability to examine confounders such as ethnicity or socioeconomic status. Certification was introduced at different phases during the pandemic for different reasons and across regional and national-level conditions with varying levels of age eligibility, supply, vaccine hesitancy, enforcement and variation in infections and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for COVID-19 infection and mortality, such as crowded living conditions, frontline jobs with high exposure to infection and low pay, dependence on public transport, low access to quality healthcare, and high rates of select chronic conditions, still characterize these groups, suggesting continued racial/ethnic disparities in COVID-19 mortality (Figueroa et al, 2021;Goldman et al, 2021;Macias Gil et al, 2020;Maness et al, 2021;Rodriguez-Diaz et al, 2020). A strategicallytargeted vaccine distribution had the potential to reduce racial/ethnic disparities in COVID-19 mortality in 2021 (Wrigley-Field et al, 2021), but many individuals faced barriers to vaccination in the early months, including difficulty scheduling vaccine appointments online, lack of transportation to vaccination sites, and lack of time off work to get vaccinated and recover from side effects (Feldman, 2021;Stone, 2021). The resulting inequitable vaccine distribution and uptake may have further exacerbated racial/ethnic disparities in COVID-19 mortality.…”
Section: Introductionmentioning
confidence: 99%